Potencial de recuperação de materiais e componentes de edificações: análise crítica em um processo de reabilitação - Silva, Roberto Caldeira da (2020)
Adapting a building to the changes and demands required by users is a task that often presents difficulties. The limitations involved are factors that lead to early obsolescence and as a result of the need for interventions or demolition. The general objective of the work is to evaluate the potential for recovery of materials and components of buildings subject to adjustments due to the end of their useful life. The scope of the research included on-site monitoring of the rehabilitation process of two medium-sized buildings, built between the 1950s and 60s, belonging to a Federal Institution of Higher Education (IFES) located in the city of Curitiba / PR. The strategy outlined was participant research (PP), combined with the technique of participant observation (OP) and data collection instruments composed of forms and photographic survey. The field investigations were divided into three phases: planning, intervention and analysis. The planning included the preparatory activities for the intervention and prediction of end-of-life scenarios. The intervention phase included monitoring the actions taken during the rehabilitation. The analyzes involved the evaluation of the breakdown and recovery operations, as well as verification of the parameters defined for the project useful life (VUP) and reporting of problems and solutions observed. The results obtained showed that the recovery potential determined for the buildings was similar, approximately 88 and 90%. In addition, 57.81m³ of landfills was recovered or diverted, equivalent to 7% of the total volume of the buildings together, disregarding what was reused on the spot. It is noteworthy that this amount, in part, was due to the successful unbundling operations, above all deconstruction and dismantling. The procedures defined in this research can be applied to small to medium-sized buildings, only in interventions related to adjustments, such as rehabilitation works, retrofits or renovations. It was concluded that the implementation of material and component recovery procedures contributes to the search for solutions that aim to increase the useful life of existing buildings and to mitigate the problem of landfill overload.